2004
DOI: 10.1029/2002jc001660
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of a coastal jet in the Long Island Sound outflow region based on HF radar and Doppler current observations

Abstract: [1] Surface current (HF radar) and velocity profile observations, obtained as part of the Front-Resolving Observational Network with Telemetry (FRONT) project over an approximately 2-year period, are used to describe the seasonal variability of a coastal jet in the Long Island Sound outflow region. The jet is observed in an area of the continental shelf where surface thermal fronts are frequently detected during both summer and winter. The current jet is coincident with a band of high summer frontal probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 26 publications
2
64
1
Order By: Relevance
“…The observations suggest the possibility that at least part of the array may have been situated on the offshore side of the peak current during spring 2002, in contrast to Figure 15c. The mean flow field is expected to have a complex horizontal structure including narrow jets associated with frontal features, and currents originating at least in part farther up-coast [Ullman and Codiga, 2004], which may be poorly resolved by the moored array. However, despite the fact that mean flow seen by the moored array does not unambiguously support the details of Figure 15c, we conclude that mean flow is the most plausible agent to explain observed near-surface seasonal ellipse changes.…”
Section: Interpreting Observed Seasonal Ellipse Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations suggest the possibility that at least part of the array may have been situated on the offshore side of the peak current during spring 2002, in contrast to Figure 15c. The mean flow field is expected to have a complex horizontal structure including narrow jets associated with frontal features, and currents originating at least in part farther up-coast [Ullman and Codiga, 2004], which may be poorly resolved by the moored array. However, despite the fact that mean flow seen by the moored array does not unambiguously support the details of Figure 15c, we conclude that mean flow is the most plausible agent to explain observed near-surface seasonal ellipse changes.…”
Section: Interpreting Observed Seasonal Ellipse Changesmentioning
confidence: 99%
“…Ship-based surveys [Kirincich, 2003] give a view of larger-scale hydrographic fields. HF radar provides good spatial resolution of both tidal flow and a seasonal jet [Ullman and Codiga, 2004] in surface currents.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between HF radar data and near-surface measurements of velocity using ADCPs suggest differences of 10-20 cm s 21 for longrange (4-5 MHz) systems with slightly reduced values of 7-10 cm s 21 for 11-13 or 24-26-MHz systems (Emery et al 2004;Ullman and Codiga 2004;Kohut et al 2006;Paduan et al 2006). Several studies have directly compared HF radar data to near-surface drifter speeds or trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Published drifter-radar velocity comparisons range from rms differences of 5-6 cm s 21 (Molcard et al 2009;Ohlmann et al 2007) to 27 cm s 21 (Barrick et al 1977). Comparisons of Lagrangian drifter and pseudodrifter trajectories by Ullman et al (2006) and Shadden et al (2009) found separations of 5-10 km after 1 day of travel, or separation speeds of 6-11 cm s 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Typical radars report results on time intervals of 0.25-1 hour, again [75, 3 depending on operating frequencies. Estimates of velocity accuracy vary widely (Emery et al 2004;Ullman and Codiga 2004;Kohut et al 2006;Paduan et al 2006), but it appears, based on very careful analysis, that perhaps 6 cm s −1 , as a root mean square difference relative to in situ ADCP (Acoustic Doppler Current Profiler) near-surface current estimates, might be a realistic minimum with current capabilities (Ohlmann et al 2007;Kirincich, de Paolo, and Terrill 2012). HF radar systems have reached a point where they are routinely employed to monitor coastal circulation around highly populated areas (e.g., Harlan et al 2010).…”
Section: A Relevant Global Observationsmentioning
confidence: 99%